Impact of the Passage of Time on the Correct Identification of the Speaker Using the Auditory Method - BRACHMAŃSKI, Stefan; HUS, Bartosz; STARONIEWICZ, Piotr (Archives of Acoustics, 2024)
Courts in Poland, as well as in most countries in the world, allow for the identification of a person on the basis of his/her voice using the so-called voice presentation method, i.e., the auditory method. This method is used in situations where there is no sound recording and the perpetrator of the criminal act was masked and the victim heard only his or her voice. However, psychologists, forensic acousticians, as well as researchers in the field of auditory perception and forensic science more broadly describe many cases in which such testimony resulted in misjudgement. This paper presents the results of an experiment designed to investigate, in a Polish language setting, the extent to which the passage of time impairs the correct identification of a person. The study showed that 31 days after the speaker’s voice was first heard, the correct identification for a female voice was 30% and for a male voice 40%.